Challenges and perspectives in the evolution of distance and online education towards higher technological environments - Julián Roa González; Natalia Sánchez Sánchez; Isaac Seoane Pujol; José L. Díaz Palencia (Cogent Education)
This article explores a proposal of continuous transformation in distance and online learning scopes in view of past, current and future emerging technologies. It traces the distance and online education from traditional learning models to the integration of advanced technology with Learning Management Systems (LMS), Artificial Intelligence (AI), and Virtual Reality (VR). The shift towards more technology-enhanced learning environments is examined within multimedia learning principles, and the challenges posed by the digital divide. This study explores a phased approach to technology integration aiming to boost interactive learning opportunities including the potential use of the metaverse. The pedagogical strategies are discussed, emphasizing the importance of addressing diverse learner needs while promoting digital literacy. This article represents the initial phase of a broader longitudinal study aimed at observing the progression in the implementation of technology in online and distance education. Future studies will delve into aspects related to the research methodology, although this work introduces general principles. The article concludes with a reflection on the future of online and distance education, advocating for continued innovation to enhance educational accessibility, engagement, and outcomes for learners globally.